On understanding the implication of pension debt on fiscal policy in Tanzania: Is there any room for improving the adequacy of pension benefits? - Josephat Lotto; Irene Isaka (Cogent Economics & Finance, 2020)
This paper aims at understanding the implication of pension debt on fiscal policy in Tanzania. The paper employed a modified projected benefit obligation (PBO) approach for a period between 2010 and 2018. The results of the paper indicate a mismatch between benefit payments and members' contributions, in that outflows are found to exceed inflows for a large part of the examined period, which tends to imply that pensions adequacy is questionable, and that the system cannot be sustained for a longer period if no rescue is put in place immediately. Further, drawing from the computed life expectancy of pensioners, it is indicative that the size of the retirement age cohort will continue to enlarge over time; which would result in increasing pension obligations. Since increased pension expenditure would not be fully covered from the existing pension assets, the Government as a guarantor would be required to cover the matured pension obligations through its annual fiscal budget. Unfortunately, looking at the current National Debt sustainability report pension debt is not part of the proposed national debt. Following these findings, and since neither increasing the contribution rate nor the retirement age may not be sustainable options, the reduction of accrual rate is the most suitable option the government is recommended to implement so as to rescue the current situation. However, in a long run, the paper recommends the government to undertake a systemic pension reform, which would change the entire pension system from a defined benefits scheme to a defined contributions scheme.
Keywords: 330; defined contribution; fiscal policy; pension benefits; pension debt